The applicability of the act on shaping the agricultural system to legal regulations governing agriculture in the Civil Code - Łobos-Kotowska, Dorota; Stańko, Marek (Przegląd Prawa Rolnego, 2020)
The considerations concern the applicability of the provisions of the Act on shaping the agricultural system to the legal regulations of agriculture contained in the civil code. The focus is on the inheritance of agricultural holdings, as well as the division of inheritance consisting of an agricultural holding, the abolition of joint ownership of an agricultural holding and the division of joint property of spouses, taking into account the provisions of the Act on shaping the agricultural system. The intention of the legislator was to ensure protection of agricultural land also in the scope of trading in agricultural real estate that has been provided for in the civil code. However, there are doubts regarding the interpretation of the terms used in both legislative acts as it leads to certain differences in the understanding of institutions defined in the code. However, this is an unacceptable situation and the provisions of special laws must not change the legal definitions of agricultural institutions guaranteeing agricultural property. This way of "amending" the civil code results in the inconsistency and dysfunctionality of the legal system.